Olefin polymers

By injecting hydrogen gas during the olefin polymerization process and introducing high crystallization zones, the problem of poor compatibility between polyolefins and polar resins and metals is solved, and the introduction of high mechanical rigidity and high crystallization zones of low-density olefin polymers is achieved.

CN116323704BActive Publication Date: 2025-04-01LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280006979.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-23
Filing Date
2022-03-23
Publication Date
2025-04-01
Estimated Expiration
2042-03-23

AI Technical Summary

Technical Problem

Polyolefins have poor compatibility and viscosity with polar resins and metals, making it difficult to mix or laminate and have low surface hydrophilicity and antistatic properties of molded products.

Method used

By injecting hydrogen into the catalyst composition for olefin polymerization, the olefin-based monomers are polymerized, and a high crystallization zone is introduced and excellent mechanical rigidity is shown.

Benefits of technology

The introduction of high mechanical rigidity and high crystallization zones of low-density olefin-based polymers is achieved, and compatibility and mechanical properties with polar materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004181638920000081
    Figure BDA0004181638920000081
  • Figure BDA0004181638920000101
    Figure BDA0004181638920000101
  • Figure BDA0004181638920000111
    Figure BDA0004181638920000111
Patent Text Reader

Abstract

This invention relates to an olefin polymer, and more specifically, to a low-density olefin polymer that incorporates highly crystalline regions and exhibits high mechanical rigidity.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2021-0037280 filed in the Korean Intellectual Property Office on March 23, 2021, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to an olefin polymer. Background Art

[0004] Polyolefin has excellent formability, heat resistance, mechanical properties, sanitary quality, water vapor permeability and appearance characteristics of molded products, and is widely used as extrusion molded products, blow molded products and injection molded products. However, the problem of polyolefin is that, in particular, polyethylene does not have polar groups in the molecule, has low compatibility with polar resins such as nylon, and has poor viscosity with polar resins and metals. Therefore, it is difficult to mix polyolefin with polar resins and metals or use with such material lamination. In addition, the molded products of polyolefin have the disadvantages of low surface hydrophilicity and antistatic performance.

[0005] In order to solve these problems and improve the affinity for polar materials, a method of grafting a monomer containing a polar group onto a polyolefin by free radical polymerization has been widely used. However, according to this method, crosslinking and molecular branching in the polyolefin molecule may be broken during the grafting reaction, and the viscosity balance between the grafted polymer and the polar resin is poor, and the miscibility between the two is low. In addition, there is a problem that the appearance characteristics of the molded product are poor due to the gel component generated by crosslinking in the molecule or foreign matter generated by the breaking of the molecular chain.

[0006] In addition, as a method for preparing olefin polymers such as ethylene homopolymers, ethylene / α-olefin copolymers, propylene homopolymers and propylene / α-olefin copolymers, a method of copolymerizing polar monomers in the presence of a metal catalyst such as a titanium catalyst and a vanadium catalyst has been used. However, in the case of copolymerizing polar monomers using such a metal catalyst, there are problems in obtaining a wide molecular weight distribution or composition distribution and low polymerization activity.

[0007] In addition, as another method, a polymerization method in the presence of a metallocene catalyst formed using a transition metal compound such as zirconium dichloride and an organic aluminum oxide compound (aluminoxane) is known. In the case of using a metallocene catalyst, a highly active olefin polymer with a high molecular weight is obtained, and the olefin polymer thus produced has a narrow molecular weight distribution and a narrow composition distribution.

[0008] In addition, as the method for preparing the polyolefin containing polar groups, it is also known to use a metallocene compound with a part of a non-crosslinked cyclopentadienyl, a crosslinked or non-crosslinked bis-indenyl or an unsubstituted indenyl / fluorenyl of ethylene crosslinking as a method for a metallocene catalyst of a catalyst. However, this method has the disadvantage that polymerization activity is extremely low. Therefore, a method for protecting polar groups by blocking groups has been carried out, but when introducing blocking groups, it is necessary to remove the blocking groups after the reaction, thereby causing a complex process.

[0009] Ansa-metallocene compounds are organometallic compounds containing two ligands connected by a bridging group, which prevents the rotation of the ligands and determines the activity and structure of the metal center.

[0010] Such ansa-metallocene compounds are used as catalysts for preparing olefin homopolymers or copolymers. In particular, it is known that ansa-metallocene compounds containing cyclopentadienyl-fluorenyl ligands can produce polyethylene having a high molecular weight and thus can control the microstructure of polypropylene.

[0011] Furthermore, it is known that ansa-type metallocene compounds containing an indenyl ligand have excellent activity and can produce polyolefins with improved stereoregularity.

[0012] As described above, various studies have been conducted on ansa-type metallocene compounds capable of controlling the microstructure of olefin-based polymers, but the extent of the studies is still insufficient.

[0013] [Prior art documents]

[0014] [Patent document]

[0015] (Patent Document 1) Korean Patent Publication No. 2007-0003071 Summary of the invention

[0016] Technical issues

[0017] An object of the present invention is to provide a low-density olefin polymer incorporating a high crystalline region and exhibiting high mechanical rigidity.

[0018] Technical Solution

[0019] In order to achieve the above-mentioned object, the present invention provides an olefin polymer satisfying the following conditions (1) to (4).

[0020] (1) Melt index (190°C, 2.16 kg load condition) is 0.1 g / 10 min to 10.0 g / 10 min,

[0021] (2) Density of 0.875 g / cc to 0.895 g / cc,

[0022] (3) the elution temperature (Te) measured by cross fractionation chromatography (CFC) is 30°C to 40°C, and

[0023] (4) When measuring CFC, 8.0≤P(75)-P(50)≤12.0 is satisfied.

[0024] Wherein, on the temperature-elution amount graph measured by CFC, P(75) and P(50) are the elution amount (weight %) in the temperature range of -20°C to 75°C, and the elution amount (weight %) in the temperature range of -20°C to 50°C, respectively.

[0025] Beneficial Effects

[0026] The olefinic polymer according to the present invention is a low-density olefinic polymer in which a high crystalline region is introduced and exhibits high mechanical rigidity. DETAILED DESCRIPTION

[0027] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0028] It will be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as the meanings defined in commonly used dictionaries. It will be further understood that the words or terms should be interpreted as having a meaning consistent with their meanings in the relevant technical context and the technical concept of the present invention based on the principle that the inventor can appropriately define the meaning of the words or terms to best explain the present invention.

[0029] The term "polymer" as used in this disclosure refers to a polymer compound prepared by polymerizing monomers of the same or different types. The commonly used term "polymer" includes the term "interpolymer" as well as "homopolymer," "copolymer," and "terpolymer." In addition, the term "interpolymer" refers to a polymer prepared by polymerizing two or more different types of monomers. The commonly used term "interpolymer" includes the term "copolymer" (usually used to refer to polymers prepared from two different monomers) and the term "terpolymer" (usually used to refer to polymers prepared from three different monomers). The term "interpolymer" includes polymers prepared by polymerizing four or more monomers.

[0030] The olefin polymer according to the present invention satisfies the following conditions (1) to (5).

[0031] (1) Melt index (190°C, 2.16 kg load condition) is 0.1 g / 10 min to 10.0 g / 10 min,

[0032] (2) Density of 0.875 g / cc to 0.895 g / cc,

[0033] (3) the elution temperature (Te) measured by cross fractionation chromatography (CFC) is 30°C to 40°C, and

[0034] (4) When measuring CFC, 8.0≤P(75)-P(50)≤12.0 is satisfied.

[0035] Wherein, on the temperature-elution amount graph measured by CFC, P(75) and P(50) are the elution amount (weight %) in the temperature range of -20°C to 75°C, and the elution amount (weight %) in the temperature range of -20°C to 50°C, respectively.

[0036] Compared with ordinary conventional olefin polymers, the olefin polymer according to the present invention has a low density and introduces a high crystalline region, and can show even higher tensile strength, bending modulus and hardness under the same level of density and melt index (190° C., 2.16 kg load condition). The olefin polymer according to the present invention is prepared by a preparation method comprising the steps of polymerizing an olefin monomer by injecting hydrogen in the presence of a catalyst composition for olefin polymerization, and introducing a high crystalline region and showing excellent mechanical rigidity according to the injection of hydrogen during polymerization.

[0037] The olefin polymer satisfies condition (1): the melt index (190° C., 2.16 kg load condition) is 0.1 g / 10 min to 10.0 g / 10 min.

[0038] The melt index (MI) can be controlled by controlling the amount of catalyst used relative to the amount of comonomer used in the process of polymerizing the olefin copolymer, and the melt index affects the mechanical properties, impact strength, and moldability of the olefin polymer.

[0039] The melt index is measured under low density conditions of 0.875 g / cc to 0.895 g / cc at 190°C and 2.16 kg load conditions according to ASTM D1238, and may be 0.1 g / 10 min to 10.0 g / 10 min, specifically, 0.3 g / 10 min or more, 0.4 g / 10 min or more, and 9.0 g / 10 min or less, 7.0 g / 10 min or less.

[0040] The olefin polymer satisfies the condition (2): the density is 0.875 g / cc to 0.895 g / cc. Specifically, the density may be 0.876 g / cc or more, 0.878 g / cc or more, and 0.892 g / cc or less, 0.891 g / cc or less.

[0041] Generally, the density of olefin polymers is affected by the type and amount of monomers used for polymerization, degree of polymerization, etc., and for copolymers, is significantly affected by the amount of comonomers. The olefin polymer of the present invention is polymerized using a catalyst composition comprising a transition metal compound having a characteristic structure, and a large amount of comonomers can be introduced, and therefore, has a low density as in the above range.

[0042] The olefin polymer satisfies the condition (3): the elution temperature (Te) measured by cross fractionation chromatography (CFC) is 30 to 40° C. The elution temperature may be specifically 31° C. or more, 32° C. or more, and 40° C. or less, 39° C. or less.

[0043] The olefin polymer satisfies condition (4): when CFC is measured, 8.0≤P(75)-P(50)≤12.0.

[0044] Here, on the temperature-elution amount graph measured by CFC, P(75) and P(50) are the elution amount (weight %) in the temperature range of -20°C to 75°C, and the elution amount (weight %) in the temperature range of -20°C to 50°C, respectively.

[0045] Satisfying P(75) and P(50) within the range of condition (4) means that the olefin polymer has a high crystalline content within the corresponding temperature range. Compared with polymers having similar elution temperatures (Te), the olefin polymer of the present invention has a high crystalline content and can improve cross-linking foaming efficiency, thereby making it possible to produce foam products with excellent mechanical properties.

[0046] If P(75) and P(50) deviate from the range of condition (4), the mechanical properties of the olefin-based polymer may be deteriorated.

[0047] P(75) and P(50) satisfying the range of condition (4) can be achieved by injecting hydrogen at 20 cc / min to 100 cc / min during the polymerization of ethylene and α-olefin monomers in the present invention. Specifically, if hydrogen is injected at the above content, the polymerization reaction can be terminated uniformly, the molecular weight distribution and the crystallinity distribution can be uniformly controlled, and the range of the corresponding condition (4) can be satisfied.

[0048] In addition, the olefin polymer satisfies the condition (5): melt flow rate ratio (MFRR, MI 10 / MI 2.16 ) is 5 to 10, which is the melt index (MI 10 , 19℃, 10kg load conditions) and melt index (MI 2.16 , 190°C, 2.15 kg load conditions), and the melt flow rate ratio can be specifically 6 or more and 9 or less, 8 or less.

[0049] According to the reduction in the number of long chain branches (LCB) of the olefin-based polymer, the melt flow rate ratio can show a lower value in the condition (5), and the mechanical properties of the polymer can be improved.

[0050] In addition, the olefin polymer satisfies the condition (6): the melting temperature (Tm) measured by differential scanning calorimetry (DSC) is 55° C. to 90° C., and specifically, the melting temperature (TM) may be 60° C. or more, 65° C. or more, and 80° C. or less, 75° C. or less. That is, 60° C. ≤ Tm ≤ 80° C., more specifically, 65° C. ≤ Tm ≤ 75° C. may be satisfied.

[0051] In addition, the olefin polymer further satisfies condition (7): the glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is -70°C to -30°C, and specifically, the glass transition temperature (Tg) may be -60°C or higher, -51°C or higher, and -43°C or lower.

[0052] Typically, the melting temperature (Tm) is measured using differential scanning calorimetry (DSC) by a first cycle comprising heating at a constant rate to a temperature about 30°C higher than the melting temperature (Tm) and cooling at a constant rate to a temperature about 30°C lower than the glass transition temperature (Tg), and a second cycle for obtaining a peak value of the standard melting temperature (Tm).

[0053] Differential scanning calorimetry (SSA) is a method of obtaining more accurate crystallization information by heating to a temperature before the peak of the melting temperature (Tm) and cooling after the first cycle using a differential scanning calorimeter (DSC), and repeatedly performing a process of heating until the temperature is decreased by about 5°C and cooling.

[0054] In the case where a small amount of high crystalline region is introduced into an olefin-based polymer, a high temperature melting peak may not be shown when the melting temperature is measured using general differential scanning calorimetry (DSC), but can be measured by differential scanning calorimetry precision measurement (SSA).

[0055] In addition, the olefin polymer according to the embodiment of the present invention can satisfy condition (8): the weight average molecular weight (Mw) is 10,000 g / mol to 500,000 g / mol, specifically, the weight average molecular weight (Mw) can be 30,000 g / mol or more, 50,000 g / mol or more, and 300,000 g / mol or less, 200,000 g / mol or less.

[0056] The weight average molecular weight (Mw) is a polystyrene-equivalent molecular weight analyzed by gel permeation chromatography (GPC).

[0057] In addition, the olefin polymer according to the embodiment of the present invention can further satisfy condition (9): the molecular weight distribution (MWD) is 0.1 to 6.0, which is the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn), and the molecular weight distribution (MWD) can specifically be 1.0 or more, 2.0 or more, and 4.0 or less, 3.0 or less.

[0058] Furthermore, the olefin-based polymer according to an embodiment of the present invention may additionally satisfy Condition (10): when cross fractionation chromatography (CFC) is measured, the soluble fraction (SF) at -20°C is 2% by weight or less.

[0059] Specifically, the soluble fraction may be 2 wt % or less, or 1 wt % or less.

[0060] When measuring the cross fractionation chromatography (CFC), the fraction eluting at low temperature has lower crystallinity, and the soluble fraction (SF) eluting below -20°C on the cross fractionation chromatography (CFC) can be regarded as an ultra-low crystalline region.

[0061] Generally, if the density of the polymer is reduced, the crystallinity may be reduced, the ultra-low crystalline region may be increased, and the impact strength may be improved. However, if the ultra-low crystalline region in the common olefin polymer is equal to or greater than a certain level, the mechanical properties may be deteriorated. The olefin polymer according to the present invention has a polycrystalline structure and has a relatively increased high crystalline content by reducing the ultra-low crystalline content, thereby showing excellent mechanical properties, such as improved tensile strength, tear strength and flexural modulus.

[0062] The olefin polymer can be selected from olefin monomers, specifically any homopolymer of α-olefin monomers, cycloolefin monomers, diene monomers, triolefin monomers, and styrene monomers, or a copolymer of two or more thereof. More specifically, the olefin polymer can be a copolymer of ethylene and an α-olefin of 3 to 12 carbon atoms, or a copolymer of ethylene and an α-olefin of 3 to 10 carbon atoms.

[0063] The α-olefin comonomer may include any one selected from propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, vinyl norbornene, 1,4-butadiene, 1,5-pentadiene, 1,6-hexadiene, styrene, α-methylstyrene, divinylbenzene and 3-chloromethylstyrene, or a mixture of two or more thereof.

[0064] More specifically, the olefin copolymer according to an embodiment of the present invention may be a copolymer of ethylene and propylene, ethylene and 1-butene, ethylene and 1-hexene, ethylene and 4-methyl-1-pentene, or ethylene and 1-octene, and more specifically, the olefin copolymer according to an embodiment of the present invention may be a copolymer of ethylene and 1-butene.

[0065] If the olefin polymer is a copolymer of ethylene and α-olefin, the amount of α-olefin may be 90 wt% or less, more specifically 70 wt% or less, further more specifically 5 wt% to 60 wt%, and further more specifically 10 wt% to 50 wt%, based on the total weight of the copolymer. If the α-olefin is contained in the above range, the above-mentioned physical properties can be easily achieved.

[0066] The olefin polymer according to the embodiment of the present invention with the above-mentioned physical properties and structural features can be prepared by continuous solution polymerization for polymerizing olefin monomers by injecting hydrogen in the presence of a metallocene catalyst composition comprising more than one transition metal compound in a single reactor. Therefore, in the olefin polymer according to the embodiment of the present invention, a block composed of more than two repeating units of any monomer in the monomers constituting the polymer is not formed in the polymer. That is, the olefin polymer according to the present invention may not include block copolymers, but may be selected from random copolymers, alternating copolymers and graft copolymers, and more specifically may be random copolymers.

[0067] Specifically, the olefin copolymer of the present invention can be obtained by a preparation method comprising the following steps: in the presence of an olefin polymerization catalyst composition comprising a transition metal compound of the following formula 1, olefin monomers are polymerized by injecting hydrogen at 20 cc / min to 100 cc / min, for example, by using a continuous stirred tank reactor in the presence of an olefin polymerization catalyst composition comprising a transition metal compound of the following formula 1, continuous solution polymerization is carried out by injecting hydrogen.

[0068] However, in the preparation of olefin polymers according to an embodiment of the present invention, it should be understood that the structural scope of the transition metal compound of Formula 1 is not limited to the specific disclosed type, but includes all changes, equivalents or substitutions included in the spirit and technical scope of the present invention.

[0069] [Formula 1]

[0070]

[0071] In formula 1,

[0072] The R1 groups are the same or different and are each independently hydrogen, an alkyl group of 1 to 20 carbon atoms, an alkenyl group of 2 to 20 carbon atoms, an aryl group, a silyl group, an alkaryl group, an aralkyl group, or a metalloid radical of a Group 4 metal substituted with a hydrocarbyl group, and two R1 groups may be linked to each other through an alkylene group containing an alkyl group of 1 to 20 carbon atoms or an aryl group of 6 to 20 carbon atoms to form a ring;

[0073] The R2 groups are the same or different and are each independently hydrogen; halogen; an alkyl group of 1 to 20 carbon atoms; an aryl group; an alkoxy group; an aryloxy group; or an acylamino group, and two or more of the R2 groups may be linked to each other to form an aliphatic ring or an aromatic ring;

[0074] The R3 groups are the same or different and are each independently hydrogen; halogen; an alkyl group of 1 to 20 carbon atoms; or a nitrogen-containing aliphatic ring or aromatic ring substituted or unsubstituted by an aryl group. In the case of the presence of multiple substituents, two or more of the substituents may be connected to form an aliphatic ring or aromatic ring;

[0075] M is a transition metal in Group 4; and

[0076] Q1 and Q2 are each independently halogen; an alkyl group of 1 to 20 carbon atoms; an alkenyl group; an aryl group; an alkaryl group; an aralkyl group; an alkylamido group of 1 to 20 carbon atoms; an arylamido group; or an alkylene group of 1 to 20 carbon atoms.

[0077] In another embodiment of the present invention, in Formula 1, R1 and R2 may be the same or different and are each independently hydrogen; an alkyl group of 1 to 20 carbon atoms; an aryl group; or a silyl group,

[0078] The R3 groups may be the same or different and may be an alkyl group of 1 to 20 carbon atoms; an alkenyl group of 2 to 20 carbon atoms; an aryl group; an alkaryl group; an aralkyl group; an alkoxy group of 1 to 20 carbon atoms; an aryloxy group; or an acylamino group, and two or more R6 groups in R6 may be linked to each other to form an aliphatic ring or an aromatic ring;

[0079] Q1 and Q2 may be the same or different and are each independently halogen; an alkyl group of 1 to 20 carbon atoms; an alkyl acylamino group of 1 to 20 carbon atoms; or an aryl acylamino group, and

[0080] M may be a transition metal in Group 4.

[0081] The transition metal compound represented by Formula 1 has the following characteristics: the metal position is connected by a cyclopentadienyl ligand introduced into tetrahydroquinoline, keeping the Cp-MN angle narrow and the Q1-M-Q2 (Q3-M-Q4) angle close to the monomer wide. In addition, according to the bonding of the ring type, Cp, tetrahydroquinoline, nitrogen and metal positions are connected in sequence to form a more stable and rigid five-membered ring structure. Therefore, when these compounds are activated by reacting with co-catalysts such as methylaluminoxane and B(C6F5)3 and then applied to olefin polymerization, polymerization of olefin polymers characterized by high activity, high molecular weight and high copolymerization performance can be achieved even at high polymerization temperatures.

[0082] The injection amount of the hydrogen injected in the step of polymerizing olefin monomers can be 20sccm to 40sccm, specifically 22sccm to 38sccm, more specifically 22sccm to 35sccm. The injection amount of hydrogen is based on the situation that the amount of ethylene injected into the reaction system is 0.87kg / h. If the injection amount of hydrogen meets the scope of the presence of the olefin polymerization catalyst composition of the transition metal compound comprising Formula 1, then the olefin polymer meeting the physical property range condition of the olefin polymer according to the embodiment of the present invention can be prepared.

[0083] Each substituent defined in the present disclosure will be explained in detail as follows.

[0084] The term "hydrocarbyl" used in the present disclosure refers to a monovalent hydrocarbon group of 1 to 20 carbon atoms consisting only of carbon and hydrogen regardless of its structure, such as alkyl, aryl, alkenyl, alkynyl, cycloalkyl, alkaryl and aralkyl, unless otherwise specified.

[0085] The term "halogen" as used in this disclosure refers to fluorine, chlorine, bromine or iodine, unless otherwise indicated.

[0086] The term "alkyl" used in the present disclosure refers to a straight-chain or branched hydrocarbon residue, unless otherwise specified.

[0087] The term "cycloalkyl" used in the present invention means a cycloalkyl group including cyclopropyl and the like, unless otherwise specified.

[0088] The term "alkenyl" used in the present disclosure refers to a straight chain or branched chain alkenyl group unless otherwise specified.

[0089] The branched chain may be an alkyl group of 1 to 20 carbon atoms; an alkenyl group of 2 to 20 carbon atoms; an aryl group of 6 to 20 carbon atoms; an alkaryl group of 7 to 20 carbon atoms; or an aralkyl group of 7 to 20 carbon atoms.

[0090] The term "aryl" used in the present invention, unless otherwise specified, means an aromatic group of 6 to 20 carbon atoms, specifically phenyl, naphthyl, anthracenyl, phenanthrenyl, The invention also includes, but is not limited to, chrysenyl, pyrenyl, anthracenyl, pyridyl, dimethylanilinyl, methoxybenzoyl and the like.

[0091] Alkaryl refers to an aryl group substituted by an alkyl group.

[0092] Aralkyl refers to an alkyl group substituted with an aryl group.

[0093] Cyclic group (or heterocyclic group) refers to a monovalent aliphatic or aromatic hydrocarbon group having 5 to 20 ring-forming carbon atoms and including one or more heteroatoms, and can be a monocyclic or condensed ring of two or more rings. In addition, the heterocyclic group may be substituted or unsubstituted by an alkyl group. Examples thereof may include indoline, tetrahydroquinoline, etc., but the present invention is not limited thereto.

[0094] The alkylamino group refers to an amino group substituted with an alkyl group, and includes a dimethylamino group, a diethylamino group, and the like, but is not limited thereto.

[0095] According to an embodiment of the present invention, the aryl group may preferably have 6 to 20 carbon atoms, and may specifically be a phenyl group, a naphthyl group, an anthracenyl group, a pyridyl group, a dimethylanilino group, an anisyl group, or the like, but is not limited thereto.

[0096] In the present invention, the silyl group may be a silyl group substituted or unsubstituted by an alkyl group of 1 to 20 carbon atoms, for example, a silyl group, a trimethylsilyl group, a triethylsilyl group, a tripropylsilyl group, a tributylsilyl group, a trihexylsilyl group, a triisopropylsilyl group, a triisobutylsilyl group, a triethoxysilyl group, a triphenylsilyl group, a tri(trimethylsilyl)silyl group, and the like, but is not limited thereto.

[0097] The compound of Formula 1 may be the following Formula 1-1, but is not limited.

[0098] [Formula 1-1]

[0099]

[0100] Furthermore, the compound may have various structures within the scope defined by Formula 1.

[0101] Due to the structural characteristics of the catalyst, the transition metal compound of Formula 1 can introduce a large amount of α-olefins and low-density polyethylene, and can prepare a low-density polyolefin copolymer at a level of 0.850 g / cc to 0.890 g / cc.

[0102] For example, the transition metal compound of Formula 1 can be prepared by, for example, the following method.

[0103] [Reaction 1]

[0104]

[0105] In Reaction 1, R1 to R3, M, Q1 and Q2 are the same as defined in Formula 1.

[0106] Formula 1 can be prepared by the method disclosed in Patent Laid-Open No. 2007-0003071, and all contents of this patent document are included in the present disclosure.

[0107] The transition metal compound of Formula 1 may be used as a catalyst for polymerization reaction as a composition type further comprising one or more of the co-catalyst compounds represented by Formula 2, Formula 3 and Formula 4 below.

[0108] [Formula 2]

[0109] -[Al(R4)-O] a -

[0110] [Formula 3]

[0111] A(R4)3

[0112] [Formula 4]

[0113] [LH] + [W(D)4] - or [L] + [W(D)4] -

[0114] In equations 2 and 3,

[0115] The R4 groups may be the same as or different from each other and are each independently selected from halogen, a hydrocarbon group of 1 to 20 carbon atoms, and a halogenated hydrocarbon group of 1 to 20 carbon atoms.

[0116] A is aluminum or boron,

[0117] The D groups are each independently an aryl group of 6 to 20 carbon atoms or an alkyl group of 1 to 20 carbon atoms in which one or more hydrogen atoms may be substituted by a substituent, wherein the substituent is at least any one selected from halogen, a hydrocarbon group of 1 to 20 carbon atoms, an alkoxy group of 1 to 20 carbon atoms, and an aryloxy group of 6 to 20 carbon atoms,

[0118] H is a hydrogen atom,

[0119] L is a neutral or cationic Lewis acid,

[0120] W is an element of Group 13, and

[0121] a is an integer greater than or equal to 2.

[0122] Examples of the compound represented by Formula 2 may include alkylaluminoxanes such as methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane and butylaluminoxane, and modified alkylaluminoxanes obtained by mixing two or more alkylaluminoxanes, specifically methylaluminoxane, modified methylaluminoxane (MMAO).

[0123] Examples of the compound represented by Formula 3 may include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide ( dimethylaluminummethoxide ), dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, tributylboron, and the like, and specifically, can be selected from trimethylaluminum, triethylaluminum, and triisobutylaluminum.

[0124] Examples of the compound represented by Formula 4 may include triethylammonium tetraphenylboron, tributylammonium tetraphenylboron, trimethylammonium tetraphenylboron, tripropylammonium tetraphenylboron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, trimethylammonium tetra(p-trifluoromethylphenyl)boron, tributylammonium tetra(pentafluorophenyl)boron, N,N-diethylaniline tetraphenylboron, N,N-diethylaniline tetra(pentafluorophenyl)boron, diethylammonium tetra(pentafluorophenyl)boron, triphenylphosphonium tetraphenylboron, trimethylphosphonium tetraphenylboron, dimethylaniline tetra(pentafluorophenyl)borate, triethylammonium tetraphenylaluminum, tributylammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o,p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetra(pentafluorophenyl)aluminum, N,N-diethylaniline tetraphenylaluminum, N,N-diethylaniline tetra(pentafluorophenyl)aluminum, diethylammonium tetra(pentafluorophenyl)aluminum, triphenylphosphonium tetraphenylaluminum, trimethylphosphonium tetraphenylaluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o,p-dimethylphenyl)boron, triphenylcarbonium tetra(p-trifluoromethylphenyl)boron, or triphenylcarbonium tetra(pentafluorophenyl)boron.

[0125] As a first method, the catalyst composition can be prepared by the following preparation method, which includes: 1) a step of obtaining a mixture by contacting a transition metal compound represented by Formula 1 with a compound represented by Formula 2 or Formula 3; and 2) a step of adding a compound represented by Formula 4 to the mixture.

[0126] In addition, as a second method, the catalyst composition may be prepared by a method in which the transition metal compound represented by Formula 1 and the compound represented by Formula 4 are brought into contact with each other.

[0127] In the first method of the preparation method of the catalyst composition, the molar ratio of the transition metal compound represented by Formula 1 to the compound represented by Formula 2 / the compound represented by Formula 2 or Formula 3 may be 1 / 5,000 to 1 / 2, specifically 1 / 1,000 to 1 / 10, more specifically 1 / 500 to 1 / 20. If the molar ratio of the transition metal compound represented by Formula 1 / the compound represented by Formula 2 or Formula 3 is greater than 1 / 2, the amount of the alkylating agent is too small, and the alkylation of the metal compound may not be completed. If the molar ratio is less than 1 / 5,000, the alkylation of the metal compound can be achieved, but due to the side reaction between the residual excess alkylating agent and the activator as the compound of Formula 4, the activation of the alkylated metal compound may not be completed. In addition, the molar ratio of the transition metal compound represented by Formula 1 / the compound represented by Formula 4 may be 1 / 25 to 1, specifically 1 / 10 to 1, more specifically 1 / 5 to 1. If the molar ratio of the transition metal compound represented by Formula 1 / the compound represented by Formula 4 is greater than 1, the amount of the activator is relatively small, and the activation of the metal compound may not be completed, and thus the activity of the catalyst composition may be deteriorated. If the molar ratio is less than 1 / 25, the activation of the metal compound may be completed, but due to the remaining excess activator, it is not economical in terms of the unit cost of the catalyst composition, or the purity of the generated polymer may be reduced.

[0128] In the second method of the preparation method of the catalyst composition, the molar ratio of the transition metal compound represented by Formula 1 / the compound represented by Formula 4 may be 1 / 10,000 to 1 / 10, specifically 1 / 5,000 to 1 / 100, more specifically 1 / 3,000 to 1 / 500. If the molar ratio is greater than 1 / 10, the amount of the activator is relatively small, and the activation of the metal compound may not be complete, and the activity of the catalyst composition thus generated may be reduced. If the molar ratio is less than 1 / 10,000, the activation of the metal compound may be fully performed, but due to the residual excess alkylating agent, it is uneconomical to consider the unit cost of the catalyst composition, or the purity of the generated polymer may be reduced.

[0129] During the preparation of the catalyst composition, as a reaction solvent, a hydrocarbon solvent such as pentane, hexane and heptane, or an aromatic solvent such as benzene and toluene may be used.

[0130] Additionally, the catalyst composition may include a supported transition metal compound and a promoter compound on a carrier.

[0131] Any carrier used in metallocene-based catalysts can be used as the carrier without particular limitation. Specifically, the carrier can be silica, silica-alumina, or silica-magnesia, and any one of them or a mixture of two or more thereof can be used.

[0132] In the case where the carrier is silicon dioxide, since the functional groups of the metallocene compound of the silicon dioxide carrier and Formula 1 can form chemical bonds, there is no catalyst to separate from the surface during olefin polymerization. As a result, the generation of fouling that polymer particles gather on the wall of the reactor or gather together during the preparation of olefin copolymers can be prevented. In addition, the particle shape and apparent density of the polymer of the olefin copolymer prepared in the presence of the catalyst comprising the silicon dioxide carrier are excellent.

[0133] More specifically, the support may be silica or silica-alumina which includes a highly reactive siloxane group and is dried at a high temperature by a method of high temperature drying or the like.

[0134] The support may also include oxide, carbonate, sulfate or nitrate components, such as Na2O, K2CO3, BaSO4 and Mg(NO3)2.

[0135] The polymerization reaction for polymerizing the olefin monomers may be achieved by a conventional process applicable to the polymerization of olefin monomers such as continuous solution polymerization, bulk polymerization, suspension polymerization, slurry polymerization and emulsion polymerization.

[0136] The polymerization reaction of the olefin monomer may be performed in an inert solvent, and as the inert solvent, benzene, toluene, xylene, cumene, heptane, cyclohexane, methylcyclohexane, methylcyclopentane, n-hexane, 1-hexene, and 1-octene may be used, but are not limited thereto.

[0137] The polymerization of the olefin polymer may be carried out at a temperature of about 25° C. to about 500° C., specifically, at a temperature of 80° C. to 250° C., more preferably at a temperature of 100° C. to 200° C. In addition, the reaction pressure during the polymerization may be 1 kgf / cm 2 Up to 150kgf / cm 2 , preferably 1kgf / cm 2 Up to 120kgf / cm 2 , more preferably 5kgf / cm 2 Up to 100kgf / cm 2 .

[0138] The olefin polymer of the present invention has improved physical properties and, therefore, can be used for blow molding, extrusion molding or injection molding in various fields and uses for packaging, construction, daily necessities, etc. including materials for automobiles, electric wires, toys, fibers and medical treatments, and specifically, for automobiles requiring excellent impact strength.

[0139] Furthermore, the olefin polymer of the present invention can be effectively used for producing shaped articles.

[0140] The molded product may be a blow molded product, an inflation molded product, a cast molded product, an extrusion laminated product, an extrusion molded product, a foam molded product, an injection molded product, a sheet, a film, a fiber, a monofilament, a nonwoven fabric, or the like.

[0141] Hereinafter, embodiments of the present invention will be explained in detail so that those skilled in the art to which the present invention belongs can easily perform. However, the present invention can be implemented in various different types and is not limited to the embodiments explained herein.

[0142] Catalyst preparation example: Preparation of transition metal compounds

[0143]

[0144] (1) Preparation of 2-methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)indoline

[0145] (i) Preparation of lithium carbamate

[0146] 2-Methylindoline (98.24mmol) and diethyl ether (150mL) are put into a Schlenk flask. The Schlenk flask is immersed in a -78°C low temperature bath obtained by dry ice and acetone and stirred for 30 minutes. Then, n-BuLi (98.24mmol) is injected by a syringe under a nitrogen atmosphere, and a light yellow slurry is formed. Then, the flask is stirred for 2 hours, and the flask temperature is raised to room temperature while removing the generated butane gas. The flask is immersed in a -78°C low temperature bath again to reduce the temperature, and CO2 gas is injected. With the injection of carbon dioxide gas, the slurry disappears into a transparent solution. The flask is connected to a bubbler, and the temperature is raised to room temperature while removing carbon dioxide gas. Afterwards, the remaining CO2 gas and solvent are removed under vacuum. After the flask is transferred to a drying oven, pentane is added thereto, then vigorously stirred and filtered, and a white solid compound, lithium carbamate, is obtained. In the white solid compound, diethyl ether forms a coordination bond.

[0147] (ii) Preparation of 2-methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)indoline

[0148] The lithium carbamate compound (2.60mmol) prepared by the above steps (i) is put into a Schlenk flask. Then, tetrahydrofuran (63.9mmol) and 45mL diethyl ether are added successively thereto. The Schlenk flask is immersed in a -20°C low temperature bath obtained by acetone and a small amount of dry ice and stirred for 30 minutes, and n-BuLi (42.60mmol) is injected. In this case, the color of the reaction mixture becomes red. While continuously maintaining -20°C, stirring is performed for 6 hours. CeCl3 2LiCl solution (42.60mmol) dissolved in tetrahydrofuran and tetramethylcyclopentanone (42.60mmol) are mixed in a syringe, and then injected into the flask under a nitrogen atmosphere. The flask temperature is slowly raised to room temperature, and the thermostat is removed after 1 hour, and the temperature is maintained at room temperature. Then, water (15mL) is added to the flask, and ethyl acetate is added, and then filtered to obtain a filtrate. The filtrate was transferred to a separatory funnel, and hydrochloric acid (2N, 80 mL) was added thereto, followed by vibration for 12 minutes. Then, a saturated sodium bicarbonate aqueous solution (160 mL) was added to neutralize, and the organic layer was extracted. Anhydrous magnesium sulfate was added to the organic layer to remove moisture, and filtered. The filtrate was taken and the solvent was removed. The filtrate thus obtained was separated by column chromatography using a solvent of hexane and ethyl acetate (v / v, 10: 1) to obtain a yellow oil. The yield was 19%.

[0149] 1 HNMR (C6D6): δ6.97 (d, J=7.2 Hz, 1H, CH), δ6.78 (d, J=8 Hz, 1H, CH), δ6.67 (t, J=7.4 Hz, 1H, CH), δ3.94 (m, 1H, quinoline-CH), δ3.51 (brs, 1H, NH), δ3.24-3.08 (m, 2H, quinoline-CH2, Cp-CH), δ2.65 (m, 1H, quinoline-CH2), δ1.89 (s, 3H, Cp-CH3), δ1.84 (s, 3H, Cp-CH3), δ1.82 (s, 3H, Cp-CH3), δ1.13 (d, J=6 Hz, 3H, quinoline-CH3), δ0.93 (3H, Cp-CH3) ppm.

[0150] (2) Preparation of [(2-methylindolin-7-yl)tetramethylcyclopentadienyl-η5,κ-N]dimethyltitanium

[0151] (i) 2-methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)-indoline (2.25 g, 8.88 mmol) and 140 mL of diethyl ether were placed in a round-bottom flask, the temperature was lowered to -30°C, and n-BuLi (17.6 mmol) was slowly added while stirring. The reaction was carried out for 6 hours while the temperature was raised to room temperature. Thereafter, the mixture was washed several times with diethyl ether and filtered to obtain a solid. The residual solvent was removed by applying a vacuum to obtain a dilithium salt compound (compound 4g) coordinated with diethyl ether (1.37 g, 50%).

[0152] 1 HNMR (pyridine-d8): δ7.22 (brs, 1H, CH), δ7.18 (d, J=6Hz, 1H, CH), δ6.32 (t, 1H, CH), δ4.61 (brs, 1H, CH ), δ3.54 (m, 1H, CH), δ3.00 (m, 1H, CH), δ2.35-2.12 (m, 13H, CH, Cp-CH3), δ1.39 (d, indoline-CH3)ppm.

[0153] (ii) In a drying oven, TiCl4·DME (4.44 mmol) and diethyl ether (150 mL) were placed in a round-bottom flask, and MeLi (8.88 mmol) was slowly added while stirring at -30°C. After stirring for 15 minutes, the dilithium salt compound (1.37 g, 4.44 mmol) prepared in the above step (i) was placed in the flask. While raising the temperature to room temperature, stirring was performed for 3 hours. After the reaction was completed, vacuum was applied to remove the solvent, and the resulting residue was then dissolved in pentane, and the filtrate was filtered to obtain the filtrate. Pentane was removed by applying vacuum to prepare a titanium compound.

[0154] 1 HNMR (C6D6): δ7.01-6.96 (m, 2H, CH), δ6.82 (t, J=7.4Hz, 1H, CH), δ4.96 (m, 1H, CH), δ2.88 (m, 1H, CH), δ2.40 (m, 1H, CH), δ2.02 (s, 3H, Cp-CH3) , δ2.01 (s, 3H, Cp-CH3), δ1.70 (s, 3H, Cp-CH3), δ1.69 (s, 3H, Cp-CH3), δ1.65 (d, J = 6.4Hz, 3H, indoline-CH3), δ0.71 (d, J = 10Hz, 6H, TiMe2-CH3) ppm.

[0155] Examples and Comparative Examples: Preparation of Olefin Polymers

[0156] Example 1

[0157] Into a 1.5L continuous process reactor, hexane solvent (7kg / h) and 1-butene (0.29kg / h) were loaded, and the temperature at the top of the reactor was preheated to 139.2°C. Triisobutyl aluminum compound (TiBAl, 0.03mmol / min), the transition metal compound obtained in the preparation example (0.28umol / min) and dimethylaniline tetrakis (pentafluorophenyl) borate cocatalyst (0.87umol / min) were injected into the reactor simultaneously. Then, hydrogen (33cc / min) and ethylene (0.87kg / h) were injected into the reactor, and copolymerization was carried out by keeping copolymerization at 139.2°C for more than 30 minutes in a continuous process at a pressure of 89bar, thereby obtaining a copolymer. Dry in a vacuum oven for more than 12 hours, and then measure physical properties.

[0158] Example 2 to Example 5

[0159] A copolymer was obtained by conducting the same copolymerization reaction as in Example 1 except that the preparation conditions in Table 1 below were changed.

[0160] Comparative Example 1

[0161] DF840 from Mitsui Chemicals Inc. was purchased and used.

[0162] Comparative Example 2

[0163] DF810 from Mitsui Chemicals Inc. was purchased and used.

[0164] Comparative Example 3

[0165] A copolymer was obtained by conducting the same copolymerization reaction as in Example 1 except that the preparation conditions in Table 1 below were changed.

[0166] [Table 1]

[0167]

[0168] Test Example 1: Analysis of olefin polymers

[0169] Regarding the copolymers of Examples and Comparative Examples, physical properties were evaluated according to the following methods, as shown in Table 2 below.

[0170] (1) Density

[0171] The measurement was performed according to ASTM D-792.

[0172] (2) Melt index (MI)

[0173] The measurement was performed according to ASTM D-1238 (Condition E, 190° C., 2.16 kg load).

[0174] (3) Melt flow rate ratio (MFRR, MI 10 / MI 2.16 )

[0175] According to ASTMD-1238 [Condition E, MI 10 (190℃, 10kg load), MI 2.16 (190℃, 2.16kg load)], measure MI 10 and MI 2.16 , M.I. 10 Divide by MI 2.16 , to calculate the melt flow rate ratio.

[0176] (4) Weight average molecular weight (MW, g / mol) and molecular weight distribution (MWD)

[0177] The number average molecular weight (Mn) and the weight average molecular weight (MW) were measured separately using gel permeation chromatography (GPC), and the molecular weight distribution was calculated by dividing the weight average molecular weight by the number average molecular weight.

[0178] - Column: PLOlexis

[0179] -Solvent: Trichlorobenzene (TCB)

[0180] -Flow rate: 1.0ml / min

[0181] - Sample concentration: 1.0mg / ml

[0182] -Injection volume: 200μL

[0183] - Column temperature: 160℃

[0184] -Detector: Agilent high temperature RI detector

[0185] -Standard: Polystyrene (calibrated by cubic function)

[0186] (5) Melting temperature (Tm) and glass transition temperature (Tg)

[0187] The melting temperature was obtained using a differential scanning calorimeter (DSC: Differential Scanning Calorimeter 250) manufactured by TAinstrument Co. That is, the temperature was raised to 150° C., maintained for 1 minute, and lowered to −100° C., and then the temperature was raised again. The DSC curve was observed.

[0188] (6) P(50), P(70) and elution temperature (Te)

[0189] Use PolymerCharCo.'s CFC as a measuring instrument. First, use o-dichlorobenzene as a solvent in an oven in a CFC analyzer to completely dissolve the polymer solution at 130°C for 60 minutes, and then introduce the solution into a TREF column controlled to 130°C. Then, the column is cooled to 95°C and stabilized for 45 minutes. Then, the temperature of the TREF column is reduced to -20°C at a rate of 0.5°C / min and maintained at -20°C for 10 minutes. After that, an infrared spectrophotometer is used to measure the elution amount (mass %). Then, the temperature of the TREF column is raised to a preset temperature at a rate of 20°C / min, and at the temperature reached, the temperature is maintained for a preset time (ie, about 27 minutes), and this work is repeated until the temperature of TREF reaches 130°C, and the amount (mass %) of the elution fraction in each temperature range is measured. In addition, in addition to sending the elution fraction at each temperature to the GPC column and using o-dichlorobenzene as a solvent, the weight average molecular weight (M) is measured by the same measurement principle as GPC. W ).

[0190] A temperature-elution amount graph was prepared and integrated, and the total elution amount was normalized to 100%. The elution amount (weight %) eluted at -20°C to 50°C was defined as P(50), and the elution amount (weight %) eluted at -20°C to 75°C was defined as P(75).

[0191] In addition, the elution temperature (Te) refers to the temperature corresponding to the top of the peak appearing after -20°C on the graph.

[0192] (7) Soluble fraction

[0193] The soluble fraction (SF) content refers to the amount of the fraction eluting below -20°C and is measured using CFC.

[0194] [Table 2]

[0195]

[0196] As shown in Table 2, the olefin copolymers according to Examples satisfy conditions (1) to (4) defined in the present invention, but Comparative Examples do not satisfy these conditions, and specifically, it is confirmed that the value of P(75)-P(50) is very small, less than 8.0.

[0197] Test Example 2: Evaluation of olefin polymers

[0198] With regard to the olefin-based polymers in Examples and Comparative Examples, physical properties were measured according to the following methods.

[0199] (1) Tensile strength and elongation

[0200] The copolymer was extruded to produce a pellet shape, and the tensile strength and elongation at break were measured according to ASTM D638 (50 mm / min).

[0201] (2) Tear strength

[0202] The copolymer was extruded to produce a pellet shape, and the tear strength at break was measured according to D624 (Type C).

[0203] (3) Flexural modulus

[0204] According to ASTM D790 standard, the measurement was carried out using INSTRON 3365 instrument.

[0205] (4) Hardness (Shore A)

[0206] The hardness was measured using a GC610 STAND durometer from TECLOCK Co. and a type A Shore durometer from Mitutoyo Co. in accordance with the standard of ASTM D2240.

[0207] [Table 3]

[0208]

[0209] As shown in the above results, it was confirmed that the olefin-based polymers of Examples showed increased mechanical rigidity, and showed improved tensile strength, tear strength, flexural modulus, hardness, and the like, when compared to Comparative Examples.

Claims

1. An olefin polymer which satisfies the following conditions (1) to (4) and (10): (1) The melt index at 190°C and 2.16 kg load is 0.1 g / 10 min to 10.0 g / 10 min. (2) Density of 0.875 g / cc to 0.895 g / cc, (3) the elution temperature (Te) measured by cross fractionation chromatography (CFC) is 30°C to 40°C, (4) when measuring the cross fractionation chromatogram (CFC), 8.0≤P(75)-P(50)≤12.0, and (10) when the cross fractionation chromatography (CFC) is measured, the soluble fraction (SF) at -20°C is 2 wt% or less, in, On the temperature-elution amount graph measured by CFC, P(75) and P(50) are the elution amount (weight %) in the temperature range of -20°C to 75°C, and the elution amount (weight %) in the temperature range of -20°C to 50°C, respectively.

2. The olefin polymer according to claim 1, wherein The olefin polymer also satisfies the following condition (5): (5) Melt flow rate ratio MI 10 / MI 2.16 5 to 10.

3. The olefin polymer according to claim 1, wherein The olefin polymer also satisfies the following condition (6): (6) The melting temperature (Tm) measured by differential scanning calorimetry (DSC) is 55°C to 90°C.

4. The olefin polymer according to claim 1, wherein The olefin polymer also satisfies the following condition (7): (7) The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is -70°C to -30°C.

5. The olefin polymer according to claim 1, wherein The olefin polymer also satisfies the following condition (8): (8) The weight average molecular weight is 10,000 g / mol to 500,000 g / mol.

6. The olefin polymer according to claim 1, wherein The olefin polymer also satisfies the following condition (9): (9) Molecular weight density (MWD) is 0.1 to 6.

0.

7. The olefin polymer according to claim 1, wherein The olefin polymer is a copolymer of ethylene and an α-olefin comonomer having 3 to 12 carbon atoms.

8. The olefin polymer according to claim 7, wherein The α-olefin comonomer is one or more selected from propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, vinyl norbornene, 1,4-butadiene, 1,5-pentadiene, 1,6-hexadiene, styrene, α-methylstyrene, divinylbenzene, and 3-chloromethylstyrene.

9. The olefin polymer according to claim 7, wherein The olefin polymer is a copolymer of ethylene and 1-butene.

Citation Information

Patent Citations

  • Automatic font generating system and method by using hand-written

    KR1020210037280A

  • Method for preparing olefin polymer using transition metal catalyst having better copolymerization

    KR101066969B1